The ACP-EU Courier - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The ACP-EU Courier, No. 192, May/June 2002 Special ´Dossier´ (number 33) containing 14 articles on various aspects of ICTs in ACP countries.